2017
DOI: 10.4103/ijpm.ijpm_466_16
|View full text |Cite
|
Sign up to set email alerts
|

An integrated genomic profile that includes copy number alterations is highly predictive of minimal residual disease status in childhood precursor B-lineage acute lymphoblastic leukemia

Abstract: These data seem to indicate that in addition to cytogenetics, CNA should be incorporated into routine clinical testing and risk algorithms for B-ALL. The IGC is of prognostic relevance and offers an additional avenue for prognostication and risk-adapted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Distinct CNA profiles were evident in B-ALL and T-ALL with both mutually exclusive and co-occurring genes. The dominance pattern of key genes affected in B-ALL cases was similar to earlier studies from India ( IKZF1, CDKN2A/B, PAX5, ETV6 ) (8, 9, 12) and different from that reported by other groups where deletions in CDKN2A/B and ETV6 were dominant (6). The new gene targets such as BTLA, CD200, VPREB1 which are associated with inferior event-free and overall survival; DMD with relapse, TBL1XR1 and TP53 with chemo-resistance; EZH2 , PAR1 region, and P2RY8-CRLF2 with poor prognosis; CASP8AP2, NF1 , and SUZ12 associated with poor response to induction therapy are included in this dMLPA panel and useful for further risk stratification in cytogenetically good risk B-ALL cases.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Distinct CNA profiles were evident in B-ALL and T-ALL with both mutually exclusive and co-occurring genes. The dominance pattern of key genes affected in B-ALL cases was similar to earlier studies from India ( IKZF1, CDKN2A/B, PAX5, ETV6 ) (8, 9, 12) and different from that reported by other groups where deletions in CDKN2A/B and ETV6 were dominant (6). The new gene targets such as BTLA, CD200, VPREB1 which are associated with inferior event-free and overall survival; DMD with relapse, TBL1XR1 and TP53 with chemo-resistance; EZH2 , PAR1 region, and P2RY8-CRLF2 with poor prognosis; CASP8AP2, NF1 , and SUZ12 associated with poor response to induction therapy are included in this dMLPA panel and useful for further risk stratification in cytogenetically good risk B-ALL cases.…”
Section: Discussionsupporting
confidence: 85%
“…Also, deletions of IKZF1 exon 4–8 associated with poor outcome although are rare but were seen in two of our samples in which this gene was affected. Earlier studies have reported the prognostic relevance of deletions in IKZF1 and EBF1 genes which are associated with MRD positivity (6, 9, 12). In our retrospective study, since IKZF1 deletions were primarily detected in BCR-ABL1 positive B-ALL cases, these cases were risk stratified into the poor risk category and were given intensive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric ALL, MRD post induction range between 25-30% (Borowitz et al, 2008;Patkar et al, 2017), in our study 13 out of 46 patients (28%) had positive MRD post induction, furthermore MRD positivity is demonstrable in 14 out of 32 patients (43.8%), and 10 out of 28 patients (35.7%) at 6 and 12 months; respectively.…”
Section: Discussionsupporting
confidence: 54%